Spectral sensitivities of the orchid bee Euglossa dilemma. (January 2023) - Dexheimer, Andreia F.; Outomuro, David; Dunlap, Aimee S.; Morehouse, Nathan I.
Graphical abstract: Highlights: This is the first study on orchid bee color vision. Orchid bees have three distinct photoreceptor types in their compound eyes. Peak sensitivities: UV (347 nm), blue (425 nm), and green (537 nm) wavelengths. This suggests that orchid bees have similar color perception to closely related bees. We found no differences between male and female E. dilemma visual systems. Abstract: Diurnal pollinators often rely on color cues to make decisions when visiting flowers. Orchid bees are major tropical pollinators, with most studies of their pollination behavior to date focusing on scent collection and chemical ecology. The objective of this study was to measure their spectral sensitivities to preliminarily characterize color vision in the orchid bee Euglossa dilemma and compare it to the known spectral sensitivity of other closely related bees. We compared E. dilemma's spectral sensitivities and opsin protein sequences to four closely related corbiculate bees. E. dilemma appears to have trichromatic vision, with spectral sensitivity peaks in the ultraviolet, blue, and green wavelengths (347 ± 0.957 (SE) nm, 429 ± 6.570 nm, and 537 ± 1.183 nm, respectively), similar to other measured bees. We found no differences between male and female E. dilemma visual systems despite neuroanatomical and behavioral differences reported in the literature. The lambda maxes of the ultraviolet-sensitive photoreceptors appeared to be the most conserved among the bees we compared. Meanwhile, both the lambda maxes of the blue photoreceptors and the blue opsin proteins sequences were the least conserved. Our results open up new possibilities for the study of color vision and color-mediated pollination behaviors in orchid bees.